Hubungan Durasi Dan Posisi Penggunaan Smartphone Terhadap Nyeri Leher Pada Mahasiswa Preklinik Fakultas Kedokteran Universitas Nusa Cendana - lai, gloria harpazo; Kareri, Dyah Gita Rambu; Amat, Anita Lidesna Shinta; Setiawan, I Made Buddy; Sasputra, I Nyoman (Cendana Medical Journal, 2023)
Background : Neck pain is an uncomfortable and painful feeling on the neck and the upper back. Neck pain are generally known by two definition, spesific neck pain and non spesific neck pain. Non spesific neck pain is caused by an injured muscle, joints, or bone in the neck area due to bad posture. Medical students used smartphones in a long duration for social media activities and learning purposes. Smartphone usage in a long duration with static and non ergonomic body position is one of the factors causing non spesific neck pain. Objective : This research’s objective is to analyze the correlation of duration and position of smartphone usage on preclinical students of The Faculty of Medicine, Universitas Nusa Cendana. Methods : This research is an analytical observational research with cross sectional approach. The samples on this research was 179 people that was obtained using stratified random sampling technique. The data was analyzed using Spearman correlation test. Results : Data from 179 respondents showed that 45.8% experienced mild neck pain, 33.0% experienced moderate neck pain, 5.0% experienced severe neck pain and 16.2% did not experience neck pain. For the duration of smartphone use, 97.8% had a high duration of smartphone use, 2.2% had a moderate duration of smartphone use and none had a low duration of smartphone use. For the position of smartphone use, 1.1% have a very high risk level, 7.8% have a high risk level, 91.1% have a medium risk level and none have a low risk level. The results of the bivariate analysis with the Spearman correlation test showed p value = 0.162 for the relationship between the duration of smartphone use and neck pain, and p = 0.538 for the relationship between the position of smartphone use and neck pain. Conclusion: There is no significant relationship between duration and position of smartphone usage on preclinical students of The Faculty of Medicine, Universitas Nusa Cendana